2023
DOI: 10.24875/gmm.m21000556
|View full text |Cite
|
Sign up to set email alerts
|

Social determinants of health associated with severity and mortality in patients with COVID-19

Abstract: Introduction: Historically, pandemics have resulted in higher mortality rates in the most vulnerable populations. Social determinants of health (SDH) have been associated with people morbidity and mortality at different levels. Objective: To determine the relationship between SDH and COVID-19 severity and mortality. Methods: Retrospective study, where data from patients with COVID-19 were collected at a public hospital in Chile. Sociodemographic variables related to structural SDH were classified according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
3

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
1
4
0
3
Order By: Relevance
“… 42 Although muscle power is considered one of the main therapeutic objectives in older adults, in patients post COVID-19, the assessment of muscle power should be within a comprehensive evaluation that considers loss of independence in activities of daily living, 43 impaired respiratory function, 44 comorbidity burden, 45 and social risk factors. 46 In this context, multidisciplinary health care teams must consider all these aspects when implementing the best strategies to improve the functionality and quality of life of COVID-19 survivors. 47 For example, considering lower extremity strengthening based on 30s-STS power findings.…”
Section: Discussionmentioning
confidence: 99%
“… 42 Although muscle power is considered one of the main therapeutic objectives in older adults, in patients post COVID-19, the assessment of muscle power should be within a comprehensive evaluation that considers loss of independence in activities of daily living, 43 impaired respiratory function, 44 comorbidity burden, 45 and social risk factors. 46 In this context, multidisciplinary health care teams must consider all these aspects when implementing the best strategies to improve the functionality and quality of life of COVID-19 survivors. 47 For example, considering lower extremity strengthening based on 30s-STS power findings.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the CCI could be added to follow-up programs, as it could help discriminate those patients who could benefit from interventions, such as physical rehabilitation or at least closer follow-up. Multidisciplinary rehabilitation teams should also be aware of the impact of social determinants of health on the severity of COVID-19 to promote strategies that improve the long-term functionality of these patients [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another critical point to consider is the influence of social determinants. Our country is not alien to this reality, and it has already been shown that these social determinants contributed to greater alteration in functioning and higher mortality in the hospitalized population ( 49 , 50 ). One of the ways to reduce this effect is the implementation of these policies at the national level involving public and private health, favoring access to the most vulnerable population.…”
Section: Discussionmentioning
confidence: 99%